Modified expandable aerosol flame retardant as well as preparation method and application thereof
By modifying the expandable graphite by silane coupling agent and phytic acid, a modified expandable aerosol flame retardant is formed, sprayed in the goaf and formed a closed space through expansion and chemical reaction, the self-ignition of coal in the goaf is solved The limitations of prevention and control have achieved more efficient prevention and control effects.
Patent Information
- Application Number
- CN202411519206.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The prior art has limitations in preventing and controlling spontaneous combustion of coal in goaf, especially in complex spatial conditions and severe air leakage, traditional grouting, gels and inhibitors are difficult to effectively deal with.
The expanded graphite is modified by silane coupling agent and phytic acid. The phytic acid is loaded on the surface of the expandable graphite by surface grafting to form a modified expandable aerosol flame retardant and spray it in the goaf area. , through the expansion of the aerosol and chemical reaction, forming a closed space to prevent coal from contacting oxygen.
A comprehensive and uniform coverage of coal spontaneous combustion in goaf has been achieved, the limitations of traditional methods have been overcome, the occurrence of spontaneous combustion in coal has been significantly reduced, and the prevention and control effect has been improved.
Smart Images

Figure CN119410028A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a modified expandable aerosol flame retardant and a preparation method thereof and application thereof in preventing and controlling spontaneous combustion of coal in goaf areas, belonging to the technical field of preventing and controlling spontaneous combustion of coal in goaf areas of coal mines in safe production of mining industries. Background Art
[0002] Coal resource suppression occupies the main position in my country's resource consumption structure, and it will not be shaken for a long time in the future. However, frequent spontaneous combustion of coal seriously threatens the safe mining of coal mines and causes a large amount of waste of coal resources. Therefore, it is very necessary to prevent and control the occurrence of spontaneous combustion of coal. Among them, more than half of coal spontaneous combustion occurs in goafs, where the spatial conditions are complex and the air leakage is serious. The current grouting, gel, and inhibitor fire prevention and extinguishing methods have certain limitations in dealing with spontaneous combustion of coal in goafs. Aerosols are considered for the prevention and control of spontaneous combustion of coal in goafs due to their unique advantages.
[0003] Chinese patent CN118638345A discloses a high-performance composite flame retardant for rigid polyurethane foam and a preparation method thereof. In the patent application, alkali treatment, silanization, and phytic acidization are used to carry out surface grafting and loading of expandable graphite. Similarly, Chinese patent CN116554555A discloses an expandable graphite / phytic acid composite flame retardant and a preparation method and application thereof. In the patent application, it is proposed to modify expandable graphite using phytic acid aqueous solution and p-aminobenzenesulfonic acid aqueous solution. The basic methods of expandable graphite flame retardants proposed in the above two patents are relatively complicated, and the solutions used therein are somewhat dangerous. The phytic acid modification method proposed in the present invention is simpler, simple to operate, and safe in composition. After modification and loading, the high-temperature stability of expandable graphite is improved. Summary of the invention
[0004] The present invention provides a modified expandable aerosol flame retardant and a preparation method thereof, and uses the aerosol flame retardant in preventing and controlling spontaneous combustion of coal in goaf areas. The purpose of the present invention is to improve the current fire prevention and extinguishing technology and address the problem of limited fire in goaf areas. The method of the present invention can isolate oxygen, greatly reduce heat release, inhibit functional group activity, and achieve more efficient prevention and control of spontaneous combustion of coal.
[0005] The present invention firstly uses silane coupling agent and phytic acid to modify expandable graphite. The surface modifier silane coupling agent will produce silanol after hydrolysis, and will produce cross-linking reaction with substances containing hydroxyl groups, and the remaining part will self-condense; the surface modifier phytic acid is a hexavalent molecule, contains a large number of hydroxyl groups, is a good cross-linking agent, and is also an excellent antioxidant; during the grafting modification process, in the ethanol solution, the silane coupling agent is hydrolyzed to produce silanol, which contacts and collides with expandable graphite particles and phytic acid molecules during continuous stirring, and the silanol and the graphite containing a large number of hydroxyl groups on the surface and the phytic acid molecules continuously undergo cross-linking reaction, and the phytic acid is loaded on the surface of the expandable graphite through continuous cross-linking reaction, so as to complete the grafting modification. The present invention sprays the modified expandable aerosol flame retardant on the goaf with spontaneous combustion phenomenon, and the aerosol will be evenly dispersed in the space, and the fine aerosol will collide with the free radicals formed by combustion, consume the participating factors of the chain reaction in the space, and at the same time be reduced by gravity and disturbance. When the aerosol approaches the combustion zone, the ambient temperature rises, the modified expandable graphite is heated, the interlayer spacing increases, and it quickly expands into a dense carbon layer that evenly covers the surface of the coal, effectively isolating oxygen. Under the continuous influence of temperature, magnesium hydroxide will decompose, while absorbing heat, it releases a large amount of water vapor. In the closed space formed by the modified expandable graphite, a short-term high temperature and humid environment is formed, and calcium hydroxide and fly ash form a hydraulic gel to block the coal space and effectively prevent coal from spontaneous combustion.
[0006] The present invention provides a modified expandable aerosol flame retardant, which is composed of the following raw materials in parts by weight: Diatomaceous earth: 3-5 parts; Phytic acid modified expandable graphite: 2~10 parts; White carbon black: 1~2 parts; Calcium hydroxide: 5-8 parts; Fly ash: 6-9 parts; Magnesium hydroxide: 5~10 parts.
[0007] The requirements for the use of the above raw materials are as follows: diatomaceous earth is AR grade, 700~900 mesh; phytic acid modified expandable graphite is 400~500 mesh; white carbon black is AR grade, of which SiO2≥90% (mass percentage), 200~300 mesh; calcium hydroxide is AR grade, 96% (purity), 300~400 mesh; fly ash is 300~400 mesh, and magnesium hydroxide is AR grade, 99% (purity), 325 mesh.
[0008] Among the above raw materials, diatomaceous earth will absorb a large amount of heat between 50℃~200℃, and at the same time will collide with free radicals in the space, reducing the activity of the free radicals, and finally forming a stable non-combustible substance that can effectively fill the tiny pores of the coal and reduce air leakage.
[0009] Phytic acid modified expandable graphite is known for its high efficiency in small amounts. When the volume of expandable graphite reaches the expansion temperature, it can expand to several to dozens of times of its original volume. It can effectively cover enough coal surface in small amounts, weaken the energy and heat exchange between coal and the surrounding environment, form a relatively isolated closed space, prevent coal from contacting oxygen, weaken the activation of coal molecules, and achieve a flame retardant effect.
[0010] Calcium hydroxide and fly ash are used as reactants. When calcium hydroxide is heated to increase sufficient water content, the two react in the closed space of the expansion layer formed to form a hydraulic gel. The gel has high hardness and is not easy to decompose. At the same time, because the particle size of the solid particles is very small, it is impossible to form a huge volume of hydraulic solid crushed coal. To a certain extent, it fills the air leakage channels of the coal and can effectively prevent the coal from contacting oxygen.
[0011] White carbon black acts as an auxiliary binder for the hydraulic gel generated when calcium hydroxide and fly ash react, which increases the connection between hydraulic gels, increases the scale and volume of hydraulic gel formation, and better fills the gaps or larger pores between coal bodies.
[0012] The phytic acid modified expandable graphite comprises a modifier and expandable graphite; the modifier is composed of phytic acid, a silane coupling agent and ethanol; the phytic acid adopts a 70% phytic acid solution, wherein the volume fraction of phytic acid is 70%; the ethanol adopts a 90% ethanol solution, wherein the mass fraction of ethanol is 90%.
[0013] The average particle size of expandable graphite is 500 mesh, and the magnification is 100ml / g~500ml / g.
[0014] The mass ratio of the expandable graphite: ethanol solution: silane coupling agent: phytic acid solution is 100:450:4:10-25.
[0015] The preparation method of the phytic acid modified expandable graphite comprises the following contents: using 90% ethanol solution, silane coupling agent (KH-550), 70% phytic acid and expandable graphite as raw materials, and adopting surface grafting method to prepare the phytic acid modified expandable graphite; the specific preparation process is as follows: After adding 500-mesh expandable graphite to a 90% by volume ethanol solution, a silane coupling agent (KH-550) was added dropwise, and then a 70% by volume phytic acid solution was added. The reaction was stirred at 600 r / min-800 r / min using a magnetic stirrer, and a solid-liquid separation filter was used to separate the solid and liquid. The filtered material was placed in an oven to dry, and the dried material was passed through a 400-mesh sieve to obtain phytic acid-modified expandable graphite.
[0016] The process of the above preparation method is further described as follows: During the above stirring reaction, a magnetic stirrer was used to stir the reaction for 60 minutes.
[0017] The above filtration process is specifically performed as follows: the solid-liquid mixture is filtered using filter paper to obtain filter residue.
[0018] The specific parameters of the drying in the oven are set as follows: vacuum drying at a temperature of 85° C. for 2.5 h.
[0019] The particle size of the phytic acid modified expandable graphite flame retardant after drying is 400 mesh to 500 mesh.
[0020] The present invention provides a method for preparing the modified expandable aerosol flame retardant, comprising the following steps: sequentially adding diatomaceous earth, white carbon black, calcium hydroxide, fly ash, magnesium hydroxide and phytic acid modified expandable graphite into a stirrer, and stirring for 10 minutes to uniformly mix the materials.
[0021] The present invention provides an application of the modified expandable aerosol flame retardant in preventing spontaneous combustion of coal in goaf areas. In the application, the phytic acid modified expandable graphite flame retardant is first made into a flame-proof aerosol, and then a variety of gaseous sols are injected into the goaf in the coal mine, and the sol colloidal particles are deposited on the surface of the coal left in the goaf, react and condense to form a network structure, and finally undergo a phase change to form a liquid colloid or a solid film with good thermal stability.
[0022] The method for preventing and controlling spontaneous combustion of coal in goafs by using a new modified expandable flame retardant aerosol provided by the present invention is to inject a new modified expandable aerosol flame retardant into goafs in coal mines where spontaneous combustion of coal is prone to occur. The aerosol is sprayed in the space by the equipment, and is deposited and evenly covers the surface of the coal under the influence of airflow and gravity. When coal spontaneous combustion occurs, heat accumulates and the temperature continues to rise. When the temperature begins to rise, the phytic acid modified expandable graphite inter-film compound is affected by the heat and spontaneously turns on chemical heat absorption to inhibit thermal runaway behavior. When the temperature reaches 50°C, the surrounding heat collision intensifies, the diatomaceous earth spontaneously absorbs heat and prevents heat transfer. When the temperature rises to around 200°C, the phytic acid modified expandable graphite absorbs enough heat, the interlayer compound is in an intensely active state, and when the expansion temperature is reached, it is rapidly decomposed to further release a large amount of SO2 and NH3 into the surrounding air, reducing the oxygen reactant content, delaying the coal-oxygen contact time, and weakening the effect of oxygen on coal activation at high temperature. The cross-linked graphite carbon layer formed after the expansion of phytic acid modified expandable graphite covers the surface of the coal seam, becoming a coating and insulating layer on the coal surface, forming a relatively independent and closed space. In the process of continuous temperature rise, the expanded graphite layer still retains a strong heat absorption capacity. When the temperature reaches 380°C, magnesium hydroxide decomposes under heat to produce non-combustible magnesium oxide and water. Limited by the closed space formed by the fluffy hydrophobic material after expansion, water vapor "envelops" the surface of the coal and contacts with the aerosol material. The output of water vapor forms a short-term high temperature and humid environment. The fly ash reacts with the contacted calcium hydroxide (5Ca(OH)2+6SiO2→5CaO·6SiO2·5H2O) to form a hydraulic gel crust on the surface of the coal, effectively filling the pores on the surface of the coal and blocking the air leakage channel.
[0023] Beneficial effects of the present invention: (1) The present invention overcomes the limitations of other fire prevention and extinguishing methods in the goaf, and achieves comprehensive and uniform coverage of the easily combustible areas in the goaf, and is suitable for complex and hidden spontaneous combustion situations.
[0024] (2) Compared with other expandable flame retardants, the modified expandable graphite of the present invention is trace and efficient, with a high expansion rate. At the same time, after modification, the density of the expandable material is increased and the heat absorption is strong.
[0025] (3) Physical and chemical effects work together. Aerosol materials have different effects at different temperatures. Diatomaceous earth absorbs heat in the early stage. When the temperature reaches 200°C, the phytic acid-modified expandable graphite has a strong expansion ability, forming a uniform thermal oxygen insulation layer on the surface of the coal, while also creating an environment for the reaction of other materials. After 380°C, magnesium hydroxide decomposes under heat to produce non-combustible magnesium oxide and water. Fly ash and contacting calcium hydroxide produce water-hardening gel and magnesium oxide, filling the gaps between coals, effectively retardant chain reactions, and achieving multiple insulation layer protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of unmodified expandable graphite after high-temperature expansion; Figure 2 This is a scanning electron microscope image of the phytic acid-modified expandable graphite obtained in Example 1 after high-temperature expansion. DETAILED DESCRIPTION
[0027] The present invention is further illustrated by the following examples, but is not limited to the following examples. Example 1
[0028] At room temperature, 4 g of 500-mesh expandable graphite was added to 18 g of 90% ethanol solution by volume, and then 0.16 g of silane coupling agent (KH-550) was added dropwise, followed by adding 0.4 g of 70% phytic acid solution by volume, and the mixture was stirred at 800 r / min using a magnetic stirrer for 1 h. The solid-liquid separation was performed using a funnel and the filtered material was placed in a constant temperature drying oven and dried at 85°C for 2.5 h to obtain the dried material, which was sieved through a 400-mesh sieve to obtain phytic acid-modified expandable graphite.
[0029] Figure 1 This is a scanning electron microscope image of unmodified expandable graphite after high-temperature expansion. It can be seen from the image that the expanded materials are dispersed with each other and no cross-linking occurs.
[0030] Figure 2 This is a scanning electron microscope image of the phytic acid-modified expandable graphite obtained in Example 1 after high-temperature expansion. It can be seen from the image that the expanded material is cross-linked.
[0031] Example 2: This example is different from Example 1 in that the amount of the 70% phytic acid solution is 0.6 g. Other aspects are the same as Example 1.
[0032] Example 3: This example is different from Example 1 in that the amount of the 70% phytic acid solution is 0.8 g. Other aspects are the same as Example 1.
[0033] Example 4: This example is different from Example 1 in that the amount of the 70% phytic acid solution is 1 g. Other aspects are the same as Example 1.
[0034] Use an electronic balance to accurately weigh the phytic acid-modified expandable graphite obtained in Examples 1 to 4, and put 0.1g of phytic acid-modified expandable graphite and original unmodified expandable graphite into a crucible, and place the crucible into an intelligent muffle furnace. Set the temperature to 800°C, open the furnace door, put the crucible containing the sample into the muffle furnace, wait for ten seconds and then open the furnace door, wait for the temperature to drop and then test it with a measuring cylinder, repeat the experiment three times, and take the average value as the expansion volume. Secondly, set the temperature range of the intelligent muffle furnace to 30°C~800°C. Observe the morphology of the expandable graphite sample after high temperature, repeat the experiment three times, take the average value as the high-temperature stable expansion volume of the expandable graphite, and weigh it with an electronic balance, repeat the experiment three times, and take the average value. The test results are as follows: Table 1
[0035] As shown in Table 1, by comparing the expandable graphite with the phytic acid modified expandable graphite of Examples 1 to 4, it can be seen that the phytic acid modified expandable graphite prepared by surface grafting of phytic acid on the expandable graphite surface has a significantly increased expansion volume. Compared with the unmodified expandable graphite, the expansion volume of Example 3 is increased by 8.56 ml / g; at the same time, the thermal stability of the expandable graphite expansion material is also increased. After high temperature, the expansion volume of the unmodified expandable graphite is only 2.69% of the original expansion volume, and Example 4 still retains 67.82% of the expansion volume.
[0036] Example 5 0.3 g of diatomaceous earth, 0.1 g of white carbon black, 0.5 g of calcium hydroxide, 0.6 g of fly ash, 0.5 g of magnesium hydroxide, and 0.2 g of modified expandable graphite were added into the blender in sequence and stirred for 10 minutes to mix the materials evenly, thereby preparing a modified expandable aerosol flame retardant.
[0037] Then, a Shanxi lignite sample was prepared: lignite was sieved through a 200-mesh sieve and vacuum dried at 45°C for 24 hours to obtain a Shanxi lignite sample. The modified expandable aerosol flame retardant and the Shanxi lignite sample were mixed at a mass ratio of 1:10, and stirred for 30 minutes to mix the samples evenly to prepare a treated coal sample.
[0038] Example 6: This example is different from Example 5 in that the amount of the modified expandable graphite is 0.4 g. Other aspects are the same as Example 5.
[0039] Example 7: This example is different from Example 5 in that the amount of the modified expandable graphite is 0.6 g. Other aspects are the same as Example 5.
[0040] Example 8: This example is different from Example 5 in that the amount of the modified expandable graphite is 0.8 g. Other aspects are the same as Example 5.
[0041] Example 9: This example is different from Example 5 in that the amount of the modified expandable graphite is 1 g. Other aspects are the same as Example 5.
[0042] The quality and heat change analysis of Shanxi lignite and the Shanxi lignite samples treated in Examples 5 to 9 were performed using a French Setaram thermal synchronous analyzer. The experimental temperature range was set at 30°C to 800°C, the heating rate was 10K / min, the test atmosphere was air, and the gas flow rate was 80ml / min. The experimental results are as follows: Table 2
[0043] Table 2 shows that the original Shanxi lignite sample is compared with the Shanxi lignite sample treated in Examples 6 to 9, and the coal sample to which the new modified intumescent flame retardant aerosol is added significantly increases the coal residual rate, indicating that the aerosol plays a synergistic role in inhibiting coal combustion during the heating process. This proves that the modified intumescent aerosol flame retardant product of the present invention can be used to prevent and control the spontaneous combustion of coal in goaf areas.
Claims
1. A modified expandable aerosol flame retardant, characterized in that The following raw materials in parts by weight composition: Diatomaceous earth: 3-5 parts; Phytic acid modified expandable graphite: 2~10 parts; White carbon black: 1~2 parts; Calcium hydroxide: 5-8 parts; Fly ash: 6-9 parts; Magnesium hydroxide: 5~10 parts.
2. The modified expandable aerosol flame retardant according to claim 1, characterized in that The requirements for the use of raw materials are as follows: diatomaceous earth is AR grade, 700~900 mesh; phytic acid modified expandable graphite is 400~500 mesh; white carbon black is AR grade, of which SiO2≥90%, 200~300 mesh; calcium hydroxide is AR grade, purity is 96%, 300~400 mesh; fly ash is 300~400 mesh, and magnesium hydroxide is AR grade, purity is 99%, 325 mesh.
3. The modified expandable aerosol flame retardant according to claim 1, characterized in that: The phytic acid modified expandable graphite comprises a modifier and expandable graphite; the modifier is composed of phytic acid, a silane coupling agent and ethanol; the phytic acid is 70% phytic acid, wherein the volume fraction of the phytic acid is 70%; the ethanol is 90% ethanol, wherein the mass fraction of the ethanol is 90%.
4. The modified expandable aerosol flame retardant according to claim 3, characterized in that: The average particle size of expandable graphite is 500 mesh, and the magnification is 100ml / g~500ml / g.
5. The modified expandable aerosol flame retardant according to claim 3, characterized in that: The mass ratio of expandable graphite: ethanol solution: silane coupling agent: phytic acid is: 100:450:4:10~25.
6. The modified expandable aerosol flame retardant according to claim 3, characterized in that: The preparation method of phytic acid modified expandable graphite comprises the following contents: using 90% ethanol solution, silane coupling agent KH-550, 70% phytic acid and expandable graphite as raw materials, and adopting surface grafting method to prepare phytic acid modified expandable graphite; the specific preparation process is as follows: After adding 500-mesh expandable graphite to a 90% by volume ethanol solution, silane coupling agent KH-550 was added dropwise, and then a 70% by volume phytic acid solution was added. The reaction was stirred at 600 r / min-800 r / min using a magnetic stirrer, and a funnel was used for solid-liquid separation and filtration. The filtered material was placed in an oven for drying to obtain a dried material, which was sieved through a 400-mesh sieve to obtain phytic acid-modified expandable graphite.
7. The modified expandable aerosol flame retardant according to claim 6, characterized in that: During the stirring reaction, a magnetic stirrer was used to stir the reaction for 60 minutes; the specific parameters for drying in an oven were set as follows: vacuum drying at a temperature of 85° C. for 2.5 hours.
8. A method for preparing the modified expandable aerosol flame retardant according to any one of claims 1 to 7, comprising the following steps: Add diatomaceous earth, white carbon black, calcium hydroxide, fly ash, magnesium hydroxide and phytic acid modified expandable graphite into the blender in sequence and stir for 10 minutes to mix the materials evenly.
9. Use of the modified expandable aerosol flame retardant according to any one of claims 1 to 7 in preventing and controlling spontaneous combustion of coal in goaf areas.
Citation Information
Patent Citations
Expandable graphite / phytic acid composite flame retardant as well as preparation method and application thereof
CN116554555A
High-performance composite flame retardant for rigid polyurethane foam and preparation method thereof
CN118638345A
Flame retardant for filtration equipment and method for improving flame retardancy in filtration equipment
JP2014530748A
Method of detecting coal spontaneous ignition at early stage
RU2407896C1